A Note on the Physical and Mechanical Properties of Maesopsis eminii Engl. (Musizi) - Ananthanarayana, A. K.; Jain, J. C. (Indian Forester, 1982)
Maesopsis eminii Engl. (musizi) an exotic species, grown in the State of Karnataka was tested for its physical and mechanical properties. The timber is c1a ssified as soft, not tough, moderately heavy and poor in retentign of shape. It is grouped under ordinary group of structural and constructional timbers. It is tentatively recommended for the manufacture of wooden crates, pent-top wooden case, light packing case and light tool handles.